The subclavian route in the resuscitation of the surgical patient - Silva, Celso (Cirugía del Uruguay, 2020)
1) The importance of the subclaviocava route as routine way of intravenous permanent infusion is emphasized. 2) The indications, technique, complications and cautions of its execution are related. 3) The importance and measure technique of P. V. C. in the management of acute circulatory failure are